The concentration of selected ions in bottled, commercial zamzam, and household water in Riyadh city and its effect on bone mineral content in growing rabbits - AlNouri, Doha Mustafa (Progress in Nutrition, 2019)
Objective: Drinking safe water is an internationally accepted human right. This objective of this study was to evaluate some of the minerals responsible for bone health in various types of water and to assess the effect of bottled water, commercial zamzam water, and tap water on bone mineral content (Ca, Mg, and Zn) in growing rabbits, as well as to identify the association between the water mineral content and bone mineral content of rabbits that had consumed various water types. Method: Samples were collected locally. Water samples were analyzed directly by the inductively coupled plasma spectrometry (ICPS), while bone (femur) samples were digested in a microwave digestion system for 30 min and then aspirated into inductively coupled plasma mass spectrometer. Result: Highest concentration of calcium was observed in commercial zamzam water followed by bottled and tap water and the zinc concentration was highest in tap water followed by commercial zamzam and bottled water. Highest concentration of magnesium was found in one of the bottled water (B3) followed by commercial zamzam, than other bottled water and least in tap water. Statistically significant differences in mineral content were observed between the various water types (p ≤ 0.05). All variety of water except zamzam provides magnesium and calcium in an amount of less than 10% of the amount recommended for children and in older people, these products supply even lower levels of the DRI of this component. Commercial zamzam and tap water provides high percentage of zinc. In bone (femur) concentration of calcium was highest in commercial zamzam water and least in bottled water. We detected significant differences when comparing the calcium content of commercial zamzam water and the other tested types (p ≤ 0.05). But the differences in the mean concentration of magnesium and zinc were statistically insignificant (p≥0.05) between all varieties. A strong and highly positive correlation (p≤0.05) was observed between bone and water calcium (R2=0.9286) and slight positive correlation was observed between bone and water magnesium (R2=0.2576). Conclusion: This study inferred that the concentration of all analyzed elements was within the guidelines set by various agencies. A large variation in various mineral concentrations has been observed in bottled water. Zamzam water provides essential minerals required for bone health. This study will help in providing more focused design of further research.